Development of predictive reliability assessment models for distribution lines improvement - Delgado, Mercedo P. (2006)
With the enactment of Republic Act 9136 or the Electric Power Industry Reform Act (EPIRA) of 2001 and the subsequent promulgation of the Philippine Distribution Code, distribution utility companies in the Philippines are required to meet reliability performance standards. Utilities, therefore must be equipped with tools on how to predict the impact of design of new distribution systems and distribution improvement projects. This will identify projects that should be implemented in order to meet customer requirements and performance targets. This research work developed predictive models for the reliability assessment of distribution circuits. Using linear regression analysis, the failure rate of distribution lines was found out to be not only a function of circuit length but also of the number of trees along the exposure of the line. The number of trees along the exposure of the distribution lines was significant factor because it could touch power lines and this could lead to a power interruption. An analysis of the causes of interruptions of the circuits showed that aside from circuit length and number of trees, several factors like effectiveness of the circuit's lightning protection, tree trimming activities, type of equipment installed affect the reliability of the distribution system.
"October 2006."
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman.
Keywords: Electric power systems -- Philippines; Electric lines -- Models. -- Philippines; Electric power distribution -- Reliability -- Standards -- Philippines; Electric power system stability